Participação da tonina na resistência à hipertrofia cardíaca induzida - Valéria Alves Fernandes (2017)
Introduction: According to the World Health Organization, cardiovascular diseases are the major cause of mortality in the world. Cardiac hypertrophy is an adaptive process in response to chronic hemodynamic overloads, representing an important risk factor for heart diseases, such as ischemia, arrhythmia and sudden death. One of the main gaps associated with the cardiovascular diseases treatment is the complexity of the events that lead to its progression and the various manifestation forms. Tonin is a serineproteinase, capable of releasing angiotensin II (Ang II). Preliminary studies from our research group have shown that transgenic mice expressing rat tonin (TGM(rTon)) are "resistant" to isoproterenol (ISO) induced cardiac hypertrophy. Objective: To identify which molecular factors and cell signaling pathways lead to cardiac hypertrophy resistance observed in the TGM(rTon) animal. Methods: TGM(rTon) and its control C57 were submitted to cardiac hypertrophy induction with ISO (20 mg / kg / day), performed during 5 days. After the induction process, the index of cardiac hypertrophy was determined. Tonina of submandibular mouse gland was purified and added to isolated neonatal cardiomyocytes from rats and subjected to hypertrophic stimulation with Ang II. In these myocytes, cell-area measurements and translocation of GRK-5 to the nucleus were performed, both by immunofluorescence. The tonin expression levels in the heart were measured by Western Blot. The expression levels of several genes related to hypertrophy were evaluated by real-time PCR, in isolated cardiomyocytes and in the TGM (rTon) heart and its control. RNA-seq was performed to identify the heart transcriptome. The libraries were pooled and sequenced at 300 cycles in the paired-end sequence, and pathway enrichment analyzes were performed using enrichr 5 tool. Results: Our data confirm TGM(rTon) cardiac hypertrophy resistance. In the isolated cardiomyocytes tonin prevent cellular hypertrophy Ang II-induced and decreased GRK-5 translocation to the myocyte nucleus. Tonin also reduced BNP, AT1 and MYH7 gene expression levels and increased gene expression levels of MAS receptor. There was no change in the ANP and GRK-5 gene expression levels. TGM(rTon) hearts presented higher tonin expression levels when compared to their control. After ISO treatment, tonin expression levels were even higher in TGM(rTon). AT1, MYH7 and BNP gene expression levels were also decreased in the TGM(rTon) heart after ISO treatment and ANP expression levels were increased. In the present study it was found that 18 genes are directly associated to cardiac hypertrophy: POSTN, CRLF1, LTBP2, SSP1, LOX, COL5A2, CTGF, NMRK2, ACTA1, MEOX1, CILP, NPPB (or BNP), THBS-4, TNC, SERPINB1A, C1QTNF3, 2200002DOIRICK and PRC1. These genes were negatively regulated in the TGM(rTon) treated with ISO compared to C57 also treated with ISO. The results were validated by q-PCR and we confirmed that POSTN, LTBP2, LOX, COL5A2, ACTA1 and NPPB were less expressed in the TGM(rTon) treated with ISO. Conclusion: Tonin, through negative regulation of several genes, plays an important cardioprotective role in preventing cardiac and cellular hypertrophy.